Effect of Aloe vera, chlorine dioxide, and chlorhexidine mouth rinses on plaque and gingivitis: A randomized controlled trial - Sravan Kumar Yeturu; Shashidhar Acharya; Arun Sreenivas Urala; Kalyana Chakravarthy Pentapati (Journal of Oral Biology and Craniofacial Research)
Objective: To evaluate the effect of Aloe vera, chlorine dioxide, and chlorhexidine mouth rinses on plaque and gingivitis in orthodontic treatment. Materials and methods: A randomized single-center, single-blind, parallel group, controlled trial was conducted among 90 subjects undergoing fixed orthodontic treatment. The subjects were randomly divided into one of the three study groups (Aloe vera, chlorhexidine, chlorine dioxide). Plaque and gingivitis were assessed using modified Silness and Loe Plaque Index and Gingival Index at baseline and at follow-up after 15 days. Paired t-test and ANOVA with post hoc Dunnett test were used. A p-value of <0.05 was considered statistically significant. Results: A total of 85 participants completed the study; among them, 40 were male and 45 were female. There was significant reduction in mean plaque and gingival scores in all the 3 groups at follow-up when compared to baseline. A significantly higher reduction (plaque and gingival scores) was found in chlorhexidine when compared with the Aloe vera group. However, no significant difference was seen between chlorhexidine and chlorine dioxide with respect to mean reduction in plaque and gingival scores. Conclusion: Chlorine dioxide can be a suitable and economical alternative for chlorhexidine. Further long-term studies are recommended for evaluating their effectiveness.